Effects of Pasture Type on Metabolism, Liver and Kidney Function, Antioxidant Status, and Plant Secondary Compounds in Plasma of Grazing, Jersey Dairy Cattle During Mid-lactation - Ford, Hunter R.; Busato, Sebastiano; Trevisi, Erminio; Muchiri, Ruth N.; van Breemen, Richard B.; Bionaz, Massimo; Ates, Serkan (Frontiers in Animal Science, 2021)
Some pasture species are rich in phytochemicals, able to improve milk yield and quality and to reduce the environmental impacts of livestock farming. The phytochemicals interact with the different gene networks within the animal, such as nuclear factor erythroid 2-related factor 2 (NRF2), but their overall impact on animal health remains to be fully understood. The objective of this study was to identify the effects of pasture Legumes and non-leguminous Forbs containing high bioactive compounds on metabolism and activity of the liver, antioxidant response, kidney function, and inflammation of dairy cows using a large array of blood parameters associated with metabolism and the innate immune system. For this purpose, 26 parameters and the concentration of certain bioactive compounds were assessed in blood plasma, collected from the Jersey cows grazing either Grass, Legume, or Forb-based pastures. In addition, serum collected from all the cows was utilized to detect the changes in NRF2 activation in bovine mammary alveolar cells (MACT) and hepatocytes. Compared with Grass, the cows that grazed both Forb and Legume pastures had lower β-hydroxybutyric acid (BHB) and creatinine and larger vitamin E and the ferric reducing ability of the plasma, supporting an improved antioxidative status for these animals. Compared with both Grass and Legume, the cows that graze Forb pasture had lower urea and urea to creatinine ratio, and lower creatinine, indicating a better kidney function. The cows grazing Legume pasture had greater hematocrit, bilirubin, cholesterol, albumin, β-carotene, retinol, and thiol groups but lower ceruloplasmin, paraoxonase, and myeloperoxidase (MPO) than those grazed Grass and Forb pastures, indicating a positive effect of Legume pasture on the liver, oxidative stress, and red blood cells. The plasma of cows in the various pastures was enriched with various isoflavonoids, especially the cows grazed on Forb and Legume pastures, which likely contributed to improving the antioxidative status of those cows. However, this effect was likely not due to the higher activation of NRF2. Overall, these results indicate that Forb and Legume pastures rich in secondary metabolites do not strongly affect the metabolism but can improve the status of the liver and the kidney and improve the efficiency of N utilization and antioxidant response, compared with the Grass pasture.